Plant-mediated synthesis of silver nanoparticles: unlocking their pharmacological potential–a comprehensive review - Dhir, Rajan; Chauhan, Sakshi; Subham, Praddiuman; Kumar, Saksham; Sharma, Pratham; Shidiki, Amrullah; Kumar, Gaurav (Frontiers in Bioengineering and Biotechnology, 2024)
In recent times, nanoparticles have experienced a significant upsurge in popularity, primarily owing to their minute size and their remarkable ability to modify physical, chemical, and biological properties. This burgeoning interest can be attributed to the expanding array of biomedical applications where nanoparticles find utility. These nanoparticles, typically ranging in size from 10 to 100 nm, exhibit diverse shapes, such as spherical, discoidal, and cylindrical configurations. These variations are not solely influenced by the manufacturing processes but are also intricately linked to interactions with surrounding stabilizing agents and initiators. Nanoparticles can be synthesized through physical or chemical methods, yet the biological approach emerges as the most sustainable and eco-friendly alternative among the three. Among the various nanoparticle types, silver nanoparticles have emerged as the most encountered and widely utilized due to their exceptional properties. What makes the synthesis of silver nanoparticles even more appealing is the application of plant-derived sources as reducing agents. This approach not only proves to be cost-effective but also significantly reduces the synthesis time. Notably, silver nanoparticles produced through plant-mediated processes have garnered considerable attention in recent years due to their notable medicinal capabilities. This comprehensive review primarily delves into the diverse medicinal attributes of silver nanoparticles synthesized using plant-mediated techniques. Encompassing antimicrobial properties, cytotoxicity, wound healing, larvicidal effects, anti-angiogenesis activity, antioxidant potential, and antiplasmodial activity, the paper extensively covers these multifaceted roles. Additionally, an endeavor is made to provide an elucidated summary of the operational mechanisms underlying the pharmacological actions of silver nanoparticles.